Hukum Bisnis Syariah dalam Perspektif Hukum Positif dan Hukum Islam - Dewi Nur Fatmah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze Islamic business law from the perspectives of Islamic law and Indonesian positive law, with particular emphasis on differences in philosophical foundations, sources of law, and regulatory objectives, as well as their implications for legal certainty and justice. This research employs a normative legal method using statutory, conceptual, and comparative approaches. The findings indicate that Islamic business law within Islamic jurisprudence is grounded in divine revelation and maqasid al-shariah, emphasizing substantive justice and public welfare, whereas Indonesian positive law primarily focuses on formal legality and legal certainty. Although there are points of convergence in protecting the interests of the parties and preventing harmful business practices, differences in the paradigms of the two legal systems may give rise to normative disharmony. Therefore, harmonization efforts are required that go beyond formal-legislative measures and are capable of internalizing the substantive values of Sharia within the national legal system.